Exploring the professional trajectories of doctors graduated from a Brazilian public university - Charles, Laurent Franck Junior; Cirino, Sérgio Dias; Barros, Delba Teixeira Rodrigues; Gianordoli-Nascimento, Ingrid Faria; Queiroz, Tatiana Pereira; Lucas, Simone Dutra (ICAReAlumni Conference Proceedings, 2020)
The main objective of this research was to investigate the professional trajectory of the alumni who graduated from the Psychology Doctoral Program at the Brazilian Universidade Federal de Minas Gerais (UFMG). Previous studies have revealed that, in the early 1980s, there were only two doctoral programs in Psychology in Brazil. In the last two decades, this number has grown exponentially and by 2019, there were 64 psychology doctoral programs in the country. This increase is beneficial in many ways, especially in terms of educational policy. However, in order to analyze the increase in doctoral programs in psychology more precisely, carefully designed studies focusing on the absorption of these doctors in the job market are needed.